Retrofitting procedures for fatigue-damaged full-scale welded bridge beams. (Research results digest (National Cooperative Highway Research Program), 1978)
"A digest of interim findings from NCHRP Project 12-15(2), "Retrofitting Procedures for Fatigue-Damaged Full-Scale Welded Beams," by John W. Fisher, Fritz Engineering Laboratory, Lehigh University."